THE INFLUENCE OF FINANCIAL LITERACY, LIFESTYLE, AND INCOME ON THE FINANCIAL BEHAVIOR OF ACCOUNTING STUDENTS AT WIJAYA KUSUMA UNIVERSITY SURABAYA - Maharani, Kendra Dima Puspa; Wany, Eva; Malludin (International Journal of Accounting Innovation, 2025)
Objective: This study aims to examine the influence of financial literacy, lifestyle, and income on the financial behavior of accounting students at Wijaya Kusuma University Surabaya. It seeks to determine the extent to which these factors contribute to shaping students' financial decision-making and management practices, highlighting the role of financial literacy in fostering responsible financial behavior. Methods: The research adopts a quantitative approach, utilizing primary data collected through questionnaires distributed via Google Forms. A sample of 44 accounting students was selected using the judgment sampling method. Data collection employed a Likert scale to measure variables, and the analysis was conducted using SmartPLS 4.0 software to test the relationships between financial literacy, lifestyle, income, and financial behavior. Results: The analysis reveals that financial literacy (X1) positively influences financial behavior (Y), indicating that students with higher financial literacy demonstrate better financial decision-making. Conversely, lifestyle (X2) and income (X3) do not significantly affect financial behavior. These findings suggest that financial behavior is more strongly linked to knowledge and understanding of financial principles rather than lifestyle choices or income levels. Novelty:  This research contributes to the understanding of financial behavior among university students by emphasizing the critical role of financial literacy. Unlike many studies that focus on broader populations, this study specifically examines accounting students, who are presumed to have some foundational knowledge of finance. The findings highlight gaps in the influence of lifestyle and income, providing a basis for further exploration of external factors and educational interventions.